Nanoscale “Chessboard” Pattern Lamellae in a Supramolecular Perylene-Diimide Polydiacetylene System - Ian J. Martin; Francis Kiranka Masese; Kuo-Chih Shih; Mu-Ping Nieh; Rajeswari M. Kasi (Molecules)
The rational design of ordered chromogenic supramolecular polymeric systems is critical for the advancement of next-generation stimuli-responsive, optical, and semiconducting materials. Previously, we reported the design of a stimuli-responsive, lamellar self-assembled platform composed of an imidazole-appended perylene diimide of varying methylene spacer length (n = 3, 4, and 6) and a commercially available diacid-functionalized diacetylene monomer, 10, 12 docosadiynedioic acid, in a 1:1 molar ratio. Herein, we expound on the importance of the composition of the imidazole-appended perylene diimide of varying methylene spacer length (n = 3, 4, and 6) and 10, 12 docosadiynedioic acid in the ratio of 2:1 to the supramolecular self-assembly, final morphology, and properties. Topochemical polymerization of the drop-cast films by UV radiation yielded blue-phase polydiacetylene formation, and subsequent thermal treatment of the films produced a thermoresponsive blue-to-red phase transformation. Differential scanning calorimetry (DSC) studies revealed a dual dependence of the methylene spacer length and stimuli treatment (UV and/or heat) on the thermal transitions of the films. Furthermore, small-angle X-ray scattering (SAXS) and wide-angle X-ray scattering (WAXS) showed well-defined hierarchical semiconducting nanostructures with interconnected “chessboard”-patterned lamellar stacking. Upon doping with an ionic liquid, the 2:1 platform showed higher ionic conductivity than the previous 1:1 one. The results presented here illustrate the importance of the composition and architecture to the ionic domain connectivity and ionic conductivity, which will have far-reaching implications for the rational design of semiconducting polymers for energy applications including fuel cells, batteries, ion-exchange membranes, and mixed ionic conductors.